Enucleation of Extraconal Frontomucocele: A Tripple-Window Approach - M, Irfan; S, Dinsuhaimi; AR, Roselinda; AS, Rani (IIUM Medical Journal Malaysia, 2009)
Mucoceles are expansile masses originating in the sinuses. They are relatively unusual, occurring most frequently at fronto-ethmoidal region. They are locally destructive. This expansile lesion caused bony erosion and displaces the adjacent structures. We report a case of a patient who presented to our clinic with bulging of his left eye and worsening of the left vision. This was preceded by history of sport injury to his left supraorbital ridge. CT scan revealed that there was an extraconal lesion at the superolateral part of the left orbital cavity which pushed the orbit inferomedially, which consistent with left frontomucocele. He underwent enucleation of the lesion via 3 windows created namely at the left supraorbital ridge, anterior table of left frontal sinus and through the septum separating the frontal sinuses.